Cambridge Certificate in Advanced English 3 with answers - Cambridge University (Cambridge university Press, 2009)
This set provides the most authentic exam preparation available, allowing candidates to familiarise themselves with the content of the exam and to practise exam techniques. Attractive colour visual material for Paper 5 is included with each test, enabling students to prepare for the paired interview (Paper 5). The Audio CD set contains the recorded material for the aural component of the exam. A Student's Book 'without answers' is also available. Some of the material for the tests in this book has been previously published in Cambridge Certificate in Advanced English 6, now updated to reflect the latest FCE exam specifications; Authentic examination papers from cambridge esol; Official preparation material for cambridge english: preliminary, also known as Certificate in Advanced english (CAE)